Bibliographic Analysis on the Financing of Education Reform in Morocco - Zineb Azar; Oussama Dardary; Malika Tridane; Said Benmokhtar; Said Belaaouad (Iraqi Journal of Science, 2021)
The National Charter for Education and Training in 1999 defined the principles, pillars and main objectives of the Moroccan education system, building on the various reforms of the early twenty-first century and the attempt to breathe new life into this reference document. Through partial and incremental changes, a total inability to tackle the root causes of the Moroccan education system and training has been revealed. This research has been conducted to answer the questions of education in the foreground national concerns and priorities in the discourse of the main political actors in Morocco that have been raised and remain interesting and can be expressed in the following question: Morocco still fails to meet the challenge of educational reform, although a large part of the state budget is allocated to this sector. Should we increase funding for education or rather improve its governance and focus on accountability?